2008
DOI: 10.1614/wt-08-077.1
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Oxyfluorfen into Strawberry (Fragaria×ananassa) Weed Management Programs

Abstract: Field trials were conducted at three California locations near Oxnard, Salinas, and Watsonville from 2002 to 2006 to evaluate broadleaf weed control and tolerance of strawberry to oxyfluorfen. Oxyfluorfen applied at 0.3 and 0.6 kg/ha before strawberry transplanting reduced densities of broadleaf weeds such as California burclover, hairy nightshade, little mallow, shepherd's-purse, and yellow sweetclover 70 to 100% compared with nontreated plots but did not control horseweed. Oxyfluorfen application resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…Application of oxyfluorfen at 400 g•ha −1 resulted in the weed control of more than 90 per cent of weeds, but the herbicide inhibited the crop growth. Several research findings showed that oxyfluorfen has successfully controlled broad leaved weeds in vegetable systems including broccoli [8], onion [9], chilli pepper [10], cauliflower [11] and cabbage [12]. Pre-emergence application of oxyfluorfen most effectively decreased the number of annual broad leaved weeds in onion and cabbage [13].…”
Section: Weed Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Application of oxyfluorfen at 400 g•ha −1 resulted in the weed control of more than 90 per cent of weeds, but the herbicide inhibited the crop growth. Several research findings showed that oxyfluorfen has successfully controlled broad leaved weeds in vegetable systems including broccoli [8], onion [9], chilli pepper [10], cauliflower [11] and cabbage [12]. Pre-emergence application of oxyfluorfen most effectively decreased the number of annual broad leaved weeds in onion and cabbage [13].…”
Section: Weed Densitymentioning
confidence: 99%
“…The crop injury was transient and appeared stunted for one month, after that the crop appeared normal. The pre-emergence application of oxyfluorfen at 300 to 600 g•ha −1 resulted in 30 per cent injury in strawberry [18]. The post-emergence application of oxyfluorfen at 150 g•ha −1 showed phytotoxicity symptoms in pea [19].…”
Section: Phytotoxicity Effect On Onionmentioning
confidence: 99%
“…A number of pre‐emergent (PRE) herbicides have been evaluated for use in strawberry . Previous studies demonstrated strawberry tolerance to PRE applications of S‐ethyl dipropylthiocarbamate (EPTC), fomesafen, pendimethalin, prodiamine, napropamide and oxyfluorfen . However, control of weeds with these PRE herbicides in strawberry has been inadequate or inconsistent .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Previous studies demonstrated strawberry tolerance to PRE applications of S-ethyl dipropylthiocarbamate (EPTC), fomesafen, pendimethalin, prodiamine, napropamide and oxyfluorfen. 5,[7][8][9] However, control of weeds with these PRE herbicides in strawberry has been inadequate or inconsistent. 6,7 For example, Yu and Boyd 6 reported that flumioxazin, fomesafen and halosulfuron suppressed Medicago lupulina emergence to 55%, 52% and 55% of the nontreated control, respectively, whereas none of these herbicides adequately suppressed G. carolinianum.…”
Section: Introductionmentioning
confidence: 99%
“…], little mallow, shepherd's purse [Capsella bursa-pastoris (L.) Medik. ], and clovers (Daugovish et al, 2008(Daugovish et al, , 2009. Stall et al (1995) found pre-emergence oxyfluorfen application at 0.3 and 0.6 kgÁha -1 did not affect strawberry vigor and provided season-long control of weeds including Carolina geranium (Geranium carolinianum L.) and cutleaf evening primrose (Oenotheria laciniata Hill.).…”
mentioning
confidence: 99%